2022
DOI: 10.3390/jcm11071824
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Telomere Length and Mitochondrial DNA Copy Number in Granulosa Cells as Predictors of Aneuploidy Rate in Young Patients

Abstract: Background: To identify the correlation among female age, cellular aging markers, and aneuploidy rate in in vitro fertilization (IVF) and the preimplantation genetic test for aneuploidy (PGT-A) cycles. Methods: This is a prospective cohort study recruiting 110 infertile women between August 2017 and July 2018. They were divided into young-age (<38 years, n = 60) and advanced-age (≥38 years, n = 50) groups. Peripheral leukocytes were assessed, and the granulosa cells were pooled during oocyte pickup. Mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In the study conducted by Yu et al, a possible connection between female age, cellular aging markers, aneuploidy rates in IVF protocols, and preimplantation genetic test for aneuploidy (PGT-A) cycles was taken into account. A negative correlation was established between TL in the granulosa cells and the aneuploidy rate in the young age group, emphasizing the need for PGT-A application in younger women [ 28 ]. Keefe et al further hypothesized that ongoing shortening of telomeres, ranging from fetal oogenesis to the adult ovary, could be the cause of age-related ovarian impairment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Yu et al, a possible connection between female age, cellular aging markers, aneuploidy rates in IVF protocols, and preimplantation genetic test for aneuploidy (PGT-A) cycles was taken into account. A negative correlation was established between TL in the granulosa cells and the aneuploidy rate in the young age group, emphasizing the need for PGT-A application in younger women [ 28 ]. Keefe et al further hypothesized that ongoing shortening of telomeres, ranging from fetal oogenesis to the adult ovary, could be the cause of age-related ovarian impairment [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telomere length is pivotal for accurate chromosomal alignment as well as adequate function of the spindle assembly checkpoint during meiosis, both of which prevent aneuploidy in embryos [ 79 ]. Shorter telomere is associated with higher rates of aneuploidy among infertile women undergoing in vitro fertilization [ 58 , 85 , 86 ]. Short telomeres impede germ cell specification by upregulating mitogen-activated protein kinase (MAPK) and transforming growth factor beta (TGF-β) signaling [ 87 ].…”
Section: Main Mechanisms Of Ovarian Agingmentioning
confidence: 99%
“…Women carrying loss-of-function variants in CHK2 manifested ANM 3.49 years later [ 10 ]. CHK2 is a downstream effector of the ATM kinase that responds primarily to DSBs, and can also be activated by the ATR kinase that responds primarily to single stranded DNA [ 86 , 120 ]. CHK2 has important functions in checkpoint signaling during the progression of the cell cycle in mitosis and meiosis [ 10 , 104 , 105 , 119 , 121 ].…”
Section: Main Mechanisms Of Ovarian Agingmentioning
confidence: 99%
“…For example, a recent study revealed that IVF success is not associated with telomere length in leukocytes [ 137 ]. Further, Yu et al (2022) demonstrated that telomere length in leukocytes cannot be used to predict aneuploidy rate as an alternative to preimplantation genetic test for aneuploidy (PGT-A) cycles [ 131 ]. Importantly, telomere length of lymphocytes does not correlate with those of oocytes, granulosa and cumulus cells [ 131 , 138 , 139 ], most likely because leukocytes are differently exposed to various factors, such as hormones, aging, and consecutive cell divisions [ 140 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Yu et al (2022) demonstrated that telomere length in leukocytes cannot be used to predict aneuploidy rate as an alternative to preimplantation genetic test for aneuploidy (PGT-A) cycles [ 131 ]. Importantly, telomere length of lymphocytes does not correlate with those of oocytes, granulosa and cumulus cells [ 131 , 138 , 139 ], most likely because leukocytes are differently exposed to various factors, such as hormones, aging, and consecutive cell divisions [ 140 ]. Consequently, controversial findings consider us that telomere length results of leukocytes should be carefully evaluated to predict developmental potentiality of oocytes and embryos.…”
Section: Introductionmentioning
confidence: 99%